Incidence, risk factors, and adverse short term perinatal and maternal outcomes associated with singleton breech presentation at delivery in Northern Tanzania - Michael Johnson Mahande; Uyonyimoo M. Mchaki; Joseph J. Obure (International Journal of Population Data Science, 2017)
ABSTRACT